O desenvolvimento de habilidades linguísticas através das mídias em espaços educacionais - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The experimental project in question aimed to work with the development of language skills, through various media, at the State High School Júlio de Castilhos, in Sant'Ana do Livramento/RS. The activities were carried out during the 2022 school year, including the involvement of final year classes and, mainly, a second year high school class. The class was proposed... activities involving the use of digital resources such as Genially that allows interaction and sharing of productions, as well as Padlet in the creation of versatile murals. To this end, practices related to the use of photography and writing were undertaken, supported by digital and printed media. It is concluded that the project was successfully carried out, resulting in the provision of creative work that covered the meaning of the objectives offered by developing ways to move the study routine and obtain meaningful learning.
Keywords: Mídia digital – Educação; Fotografia; Educação; Aquisição de linguagem; Digital Media – Education; Photography; CNPQ::CIENCIAS SOCIAIS APLICADAS